Advanced Practice Providers' Perceptions of Patient Workload: Results of a Multi-Institutional Survey. (October 2016) - Kapu, April N.; McComiskey, Carmel A.; Buckler, Lacey; Derkazarian, Jennifer; Goda, Tammy; Lofgren, Maria A.; McIlvennan, Colleen K.; Raaum, Julie; Selig, Patricia M.; Sicoutris, Corinna; Todd, Barbara; Turner, Vicki; et al.
Abstract : OBJECTIVE: This study examines data collected from a survey of advanced practice providers' (APPs') perceptions of reasonable versus actual APP-to-patient ratios and other factors that affect workload burden in both inpatient and outpatient clinical settings. BACKGROUND: Advanced practice providers provide accessible, cost-effective, and quality care in a growing number of specialty practices across multiple patient care settings. They are caring for higher volumes of patients and assuming more responsibilities while continuing to navigate highly complex healthcare systems. Limited evidence or benchmark data exist that would assist in determining optimal workload and staffing models that include APPs. METHODS: A group of advanced practice leaders developed and distributed a 43-question survey of workload factors to a highly diverse APP workforce. RESULTS: There were 1466 APPs across 37 areas of practice who responded to the survey distributed in 14 separate organizations. The perceived reasonable workload was lower than the actual workload for 22 specialty practice areas. The analysis included years of experience as an APP, work hours, on-call commitment, nonclinical responsibilities, and time spent in documentation, direct patient care, and performing procedures. CONCLUSIONS: There is a consensus among APPs, within their practice area, about what constitutes a reasonable patient assignment, despite the variability in APP experience, organizational culture, processes, and patient acuity.